1999
DOI: 10.1007/s004310051167
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD69 on T-cells from HIV-1-infected children and adolescents increases with increasing viral load

Abstract: We evaluated the use of a whole-blood assay that measures spontaneous and activation-induced CD69 expression on peripheral blood T-cells in vitro for assessment of T-cell function in HIV-1-infected paediatric patients. Heparinized venous blood from 28 HIV-1 positive children and adolescents and 23 healthy controls was incubated for 4 h with or without 5 microg/ml phytohaemagglutinin (PHA). Thereafter, analysis of CD69 expression on CD4+ and CD8+ T-cells was done by flow cytometry; simultaneously we determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
(30 reference statements)
1
6
0
1
Order By: Relevance
“…In our present study, the levels of CD69 expression on CD3+ subsets did not differ between the HIV positive and HIV negative control groups. This supports the observation by Krowka et al and Böhler et al [53, 54] that unstimulated T-cells from HIV- infected and negative control individuals exhibited similar levels of CD69 expression [53, 54]. The reduced proportions of T-lymphocytes coexpressing CD69 were seen only upon mitogen stimulation in HIV-infected adults [53].…”
Section: Discussionsupporting
confidence: 85%
“…In our present study, the levels of CD69 expression on CD3+ subsets did not differ between the HIV positive and HIV negative control groups. This supports the observation by Krowka et al and Böhler et al [53, 54] that unstimulated T-cells from HIV- infected and negative control individuals exhibited similar levels of CD69 expression [53, 54]. The reduced proportions of T-lymphocytes coexpressing CD69 were seen only upon mitogen stimulation in HIV-infected adults [53].…”
Section: Discussionsupporting
confidence: 85%
“…Though CD69 is rapidly expressed in viral infections (17)(18)(19), its role in the immune response to these infections has never been studied to date. We aimed at analyzing the effect of CD69 deficiency on the course of VACV infection, and we found that CD69 deficiency results in increased early NK cell-dependent control of the infection.…”
mentioning
confidence: 99%
“…CD69 has been found to be rapidly upregulated on all the leukocyte lineages studied, upon activation with the corresponding stimuli (14). CD69 expression has also been reported in infections (32)(33)(34)(35). Earlier studies showed that CD69 regulates the immune response by modulating the expression of various cytokines.…”
Section: Discussionmentioning
confidence: 86%